ROAD PERFORMANCE ANALYSIS WITH MEDIAN AND WITHOUT MEDIAN ON THE ROAD OF A.YANI SATUI - Abdy Herwandy (Universitas Lambung Mangkurat, 2020)
The road that is located in the City of Satui is a road that connects cities that are large in the South Kalimantan, the road is often used by mining trucks. From these conditions, there will be a high movement of people, goods, and services. For this reason, it is necessary to conduct a review to determine the performance of the road.The location in this study is on A.Yani Street, City of Satui, South Kalimantan. On this road, there is a part of the road that has a median and does not have a median. Data collected from the results of traffic surveys are primary data which includes geometric data, traffic volume data, and traffic speed data. Secondary data which includes an overview of the study area. The data obtained are then grouped according to the composition of the vehicle. Then the data is made into hourly traffic data to get volume, speed, and density. The data obtained was analyzed to obtain capacity, the appropriate relationship model, and performance changes between roads.The results of data analysis on A.Yani Street, City of Satui are the maximum volumes obtained on the road with a median of 468,75 amp/hour while those on the road without the median are 421,51 amp/hour. The maximum density obtained on the road with a median of 133,67 SMP/km while on the road without a median of 55,86 SMP/km. The maximum speed obtained on the road without the median is 129,2 km/hour while the road with the median maximum speed is 60,87 km/hour. The corresponding equation for A.Yani Street, the City of Satui on the road with the median is the Underwood model, y = 61,161e-0,048x with the R-value of 0,90675 while the road without the median is the Greenberg model, y = -20,41ln(x) + 82,208 with an R-value of 0,90161.